The Role of Fort Asa City as a Basic Defense of The Bima Kingdom in 1667 - Subari, Subari; Anwar, Anwar (Yupa: Historical Studies Journal, 2024)
The resistance of the Bima people in defending the kingdom's territory from Dutch colonial colonialism has taken quite a long time, where Asakota Fort has an important role as a maritime defense strategy. The aim of this research is to find out the struggle of the Bima people against the VOC (Verenigde Oost Indische) government from the territory of the Bima kingdom. The results of the research show that the Asakota Fortress had an important role in defending the naval resistance attacks between the Bima kingdom and the VOC government, because it was located in a strategic place to repel VOC warships that wanted to enter the Bima kingdom's territory. Asakota Fort was built during the time of Sultan Abdul Khair Sirajuddin as a sea defense fort at the entrance to the Bima kingdom. At that time the Gowa-Tallo kingdom had been defeated by the Dutch Company and ended with the Bongaya agreement.